2019
DOI: 10.3389/fimmu.2019.00670
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines: Key Determinants of Resistance or Disease Progression in Visceral Leishmaniasis: Opportunities for Novel Diagnostics and Immunotherapy

Abstract: Leishmaniasis is a parasitic disease of humans, highly prevalent in parts of the tropics, subtropics, and southern Europe. The disease mainly occurs in three different clinical forms namely cutaneous, mucocutaneous, and visceral leishmaniasis (VL). The VL affects several internal organs and is the deadliest form of the disease. Epidemiology and clinical manifestations of VL are variable based on the vector, parasite (e.g., species, strains, and antigen diversity), host (e.g., genetic background, nutrition, div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
124
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 310 publications
2
124
0
4
Order By: Relevance
“…In respect to the immunological response, it has been observed that in visceral leishmaniasis, parasites downregulate IFN-γ, a Th1 related cytokine, and in contrast upregulate IL-10, a T regulatory associated cytokine [ 36 , 37 ]. Thus, a low or absent level of circulating IFN-γ will not activate macrophage to a leishmanicidal state; additionally, IL-10 is able to inhibit macrophage activation, and is associated with parasite persistence in the host tissues [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In respect to the immunological response, it has been observed that in visceral leishmaniasis, parasites downregulate IFN-γ, a Th1 related cytokine, and in contrast upregulate IL-10, a T regulatory associated cytokine [ 36 , 37 ]. Thus, a low or absent level of circulating IFN-γ will not activate macrophage to a leishmanicidal state; additionally, IL-10 is able to inhibit macrophage activation, and is associated with parasite persistence in the host tissues [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…with the control of disease caused by Leishmania donovani complex (35). In a recent study, we demonstrated that FML increases the levels of both IL-12p70 and IL-10 in activated macrophages (19).…”
Section: Discussionmentioning
confidence: 93%
“…VL is characterized by the absence of cytokines such as IFN-γ and IL-12 and cure of VL is associated with a restoration of these cytokines (34). Several reports have shown that IL-10 and IL-12 play opposite roles in control of VL infections (35). The IL-10 is associated with progression VL and IL-12…”
Section: Discussionmentioning
confidence: 99%
“…The next step we will follow will be the evaluation of the vaccine candidate in the context of a visceral disease model (e.g. L. infantum transmission by L. longipalpis , the natural parasite-vector pairing from South America), with a certain degree of optimism, since also in visceral disease, a high IFN-γ response, together with a lower IL-10 response are essential for parasite elimination and disease resolution 67 , 68 .…”
Section: Discussionmentioning
confidence: 99%